Differences in the internal structure of hallucinatory experiences between clinical and nonclinical populations. Issue 1 (30th March 2015) - Chang, Jae Seung; Kim, Yeni; Kim, Se Hyun; Hwang, Samuel; Kim, Jayoun; Chung, In-Won; Kim, Yong Sik; Jung, Hee-Yeon
Abstract: We investigated differential patterns of hallucinatory experiences between nonclinical and clinical samples. A total of 223 nonclinical individuals (108 females) and 111 subjects with schizophrenia (54 females) completed the Launay–Slade Hallucination Scale-Revised (LSHS-R) and Perceptual Aberration Scale (PAS). The Minnesota Multiphasic Personality Inventory-2 (MMPI-2) was used for the nonclinical group, and the Positive and Negative Syndrome Scale (PANSS) hallucination item was used for the clinical group. Cronbach׳s alpha values showed good internal consistency for the LSHS-R. In the two groups, significant associations were found between LSHS-R and PAS scores. Two factors were extracted through a principal component analysis (PCA) in the nonclinical group, and three factors were identified in the clinical group. The results of a hierarchical cluster analysis (HCA) revealed that a perception–cognition dimension was clear cluster discriminating element for the nonclinical group, whereas alterations in perception–cognition dimension were characteristic in cluster structure of the clinical group. Our findings suggest that the nature of hallucinatory experiences may differ qualitatively between a nonclinical population and subjects with schizophrenia. Perceptual or cognitive aberrations may add a psychopathologic dimension to hallucinatory experiences. Exploring the internal structure of hallucinatory experiences may provide explanatory insight into these experiences in the general population. Highlights: Hallucinatory experiences differ qualitatively between nonclinical and clinical samples. Perception–cognition dimension is clear in hallucinations of nonclinical population. Disturbed perceptual-cognitive dimension is evident in hallucinations of clinical population. Korean LSHS-R is sensitive to qualitative aspects of hallucinatory experiences.